Samarbeid om selvhjelp En antologi om den nye selvhjelpsbevegelsen i Norge - Gotaas, Nora (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2019)
"The development and spread of self-help groups in Norway has been unlike that in other western countries. Public authorities, in collaboration with private sector volunteer resources, have created a national hybrid organization, Self-Help Norway (Selvhjelp Norge), to promote 'self-help' options. The introduction of combined groups, in which participants come together with a range of different problems or diagnoses, is also unusual. This book takes a closer look at the phenomenon of self-help in light of theories relating to group therapy, social movements, organizational sociology and welfare-state development. The individual chapters are based on the authors' own research on self-help groups and the way they are organized in Norway. Our underlying point of departure is that self-help is in fact something quite different from the common public perception of a self-absorbed and 'narcissistic' activity that occurs at the expense of the community. Self-help groups have, rightly so, a focus on individual change and have recently gained a stronger psychological orientation. There is however a need for describing and analyzing the self-help group's collective dimension, the reciprocal form of self-help that takes place in the context of the group. We analyze as well the growth of what we have called 'the new self-help movement' in the border zone between public and private sector and show how self-help has been established in various local societies as a form of social entrepreneurship. The movement's breakthrough with the public sector is internationally unique, but it can also have come at a cost in the form of less legitimacy and relevance for the other self-help organizations. We pose questions about where these developments will lead."